Evaluation of Improved Stove Programs in Guatemala : Final Report of Project Case Studies - Álvarez, Danilo; Palma, Carolina; Tay, Manuel (World Bank, Washington, DC, 2014)
This report presents the results of a study conducted by Fundación Solar-a Guatemalan nongovernmental organization (NGO) that works in the field of renewable energy-on experiences from improved-stove programs in Guatemala. The goal of the study was to systematically evaluate selected projects to determine success factors, sound practices that could be replicated elsewhere, and weaknesses to avoid. Fundación Solar's research team studied three projects, implemented by three respective organizations, on improved, wood-conserving stoves in Guatemala. To acquire needed information, the team conducted interviews and focus groups with stakeholders in the respective geographic regions-Baja Verapaz, Jalapa, and San Marcos-in which the three projects were implemented. This report includes the findings, conclusions, and recommendations that resulted from the three cases studied.